The Role of Human Resource Competency in Improving the Quality of Financial Statements: A Literature Review - Fitria Dwinanda; Firman Tatariyanto; Sugiyanto Sugiyanto (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study is motivated by the increasing demand for financial reporting that is reliable, transparent, and compliant with accounting standards, positioning financial statement quality as a strategic issue for organizational accountability. The study aims to analyze the role of human resource (HR) competency in improving the quality of financial statements through a Systematic Literature Review (SLR) approach. An SLR was conducted by reviewing 60 scholarly articles retrieved from reputable databases Scopus, ScienceDirect, and Google Scholar and analyzing them through identification, selection, and synthesis stages guided by the PICO (Population, Intervention, Comparison, Outcome) framework; coding and thematic analysis were supported by NVivo software. The synthesis indicates that HR competency encompassing accounting knowledge, technical skills, and professional attitudes plays a significant role in enhancing financial statement quality and strengthening compliance with PSAK-based reporting practices. In addition, competency gaps are identified as a primary factor that reduces reporting accuracy and hinders the fulfillment of PSAK requirements, particularly when technology adoption and internal control implementation are not matched by adequate capability. HR competency development is facilitated by continuous education and training, effective standard implementation, appropriate utilization of information technology, leadership commitment, and robust internal control systems. Accordingly, strengthening HR competency constitutes a critical prerequisite for improving accountability and the quality of financial reporting, while also offering theoretical implications and practical recommendations for organizations and policymakers in designing sustainable competency development strategies.